Konsep Pembelajaran Ilmu Tajwid Dalam Kitab Hidayatus Shibyan - Novandi Abdur Roozaq; Jaenal Abidin (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2022)
The Hidayatus Shibyan book is one of the guidelines for recitation of tajwid used in non-formal institutions such as Islamic boarding schools. This book discusses nadzaman which contains the basics of recitation. Hidayatus Shibyan's book has an influence on the understanding of recitation. The purpose of this study was to determine the implementation of tajwid learning in the Hidayatus Shibyan book and the influencing factors in the implementation of tajwid learning in the Hidayatus Shibyan book. The result of the research is that the implementation of tajwid learning can be done through non-formal institutions such as Islamic boarding schools, which will be guided by teachers or commonly called kiyai. The factors that influence the learning of tajwid are teacher factors and student factors, the teacher factor must have a good teaching method so that it can create a sense of interest in students for learning recitation of tajwid, the teacher also plays a role in teaching tajwid science lessons, because the teacher has sufficient material insight to train students, the factor of the students is from the students' own interests, where interest is the physical condition of the students' spirituality, where this interest is an interest, motivation in the learning process of tajwid.